(untitled) (Annals of Medical Research, 2021)
Aim: We aimed to investigate platelet and associated parameters’ changes, such as mean platelet volume, platelet distribution width, and platecrit, in tertiary respiratory intensive care unit (ICU) patients. Materials and Methods: This is a retrospective observational study. It’s conducted between August 1, 2018 and February 1, 2019. Demographic variables, such as, age, gender, admission diagnosis, admission site, Acute Physiology and Chronic Health Evaluation Score-II (APACHE-II), Sequential Organ Failure Score (SOFA), mechanical ventilation (MV) need, multiple organ failure (MOF) status at admission, renal replacement therapy (RRT) need, and laboratory variables of platelet (PLT), mean platelet volume (MPV), platelet distribution width (PDW) and platecrit (PCT) were recorded. Patients under age 18, or had more than one intensive care unit admission, or lack of whole-records were excluded from the study.Results: There were 132 patients included in the study. Mean age was 72±12.64 years and 50.4% of patients were male. Pneumonia was the most frequent admission diagnosis (32.6%) and patients admitted to ICU mostly from emergency department (86.4%). Mean APACHE-II and SOFA scores were 17(3-20) and 5(3-7), respectively. Invasive MV need, MOF status, vasoactive drug need and RRT need were found significant for increased mortality rate. Mean values of PLT, MPV, PDW and PCT levels were 225.02±94.85x103µL, 10.95±1.0 fL, 13.0±1.47 fL and 0.26±0.07 %, respectively. PLT and MPV levels were found related to increased mortality rate. Conclusion: PLT and MPV levels could be helpful for physicians in need for early prognostication in the respiratory intensive care unit at admission.